"That's Me I am the Farmer of the Land": Exploring Identities, Masculinities, and Health Among Male Farmers' in Ireland. Issue 4 (August 2021) - Hammersley, Conor; Richardson, Noel; Meredith, David; Carroll, Paula; McNamara, John
Compared to other occupational groups, farmers in Ireland experience a disproportionate burden of health problems, which impact farmers' livelihoods and farming sustainability. Internationally, farmers' poor health outcomes are associated with intersecting economic, environmental, socio-cultural, and occupation-specific factors linked to changes in agricultural governance. This qualitative study explored the challenges and stressors facing farmers in Ireland and how changes in farming governance have impacted farmers' identities, masculinities and health. Eleven focus groups ( n = 26 female, n = 35 male, age-range 20s–70s) were conducted with both male farmers ( n = 3 focus groups; n = 13) and key informants ( n = 8 focus groups; n = 48, 22 male, 26 female). Utilizing Thematic Content Analysis, transcripts were coded independently by the first and second author using open and comparative coding techniques, with emerging themes grouped into primary and subthemes. Theme memos and conceptual maps tracked evolving relationships between themes. The analysis identified three broad themes. "Wrestling with challenges to autonomy and control within farming" examines the impact of tighter regulatory frameworks associated with changes to farming governance and unpacks other challenges associated with scale and succession. "Farming masculinities and health" explores how farming masculinities were closely aligned with farming practices and health practices and were framed relationally. "Isolation and the demise of rural communities" considers the impact of reduced social interaction on loneliness among farmers, particularly among more "at risk" single and older farmers. Findings provide unique insights into contemporary challenges and stressors facing farmers and have important implications for informing the design and roll-out of a national farmers' health training program.